#TITLE_ALTERNATIVE# - ARINILHAQ (NIM : 102 08 026); Pembimbing : Dr. Rena Widita
Retinal diseases are caused by a disturbance in the retina that inhibit sensor light stimulus recipients. One of the factors that influence is a change in the thickness of the retina, either thickening or erosion of the surface of the retina. Changes in retinal thickness can be seen from the results of the medical image acquisition with Optical Coherence Tomography. Examination of this type generate two-dimensional retinal image of a point of acquisition. The resulting image can only illustrate the retina a cross section at certain angles. Ophthamologis should review some of the two-dimensional retinal images separately to see the whole image of the surface of the macula. This would impede the diagnosis process of the disease. Therefore, this study developed a method that combines and reconstruct 2-dimensional retinal images into three-dimensional images to display volumetric macular accurately. By using the reference normal macular thickness distribution, system provide an overview map of irregularities macula. The system is built with three main stages: data acquisition, data extraction and 3-dimensional reconstruction. At data acquisition step,Optical Coherence Tomography produced six *.jpg images of each patient were further extracted with MATLAB 2010a software into six one-dimensional array. The six arrays are combined into a 3-dimensional matrix using a kriging interpolation method with SURFER9 resulting 3-dimensional graphics of macula. Finally, system provides three-dimensional color graphs based on the data distribution normal macula. Reconstruction system built with the software MATLAB 2010a and SURFER9 produces three-dimensional images that can show not only the thickness of the macula in each direction, but also a map of the distribution of macular thickness deviation.